MODERATING ROLE OF THE VILLAGE CONSULTATIVE BODY IN QUALITY OF VILLAGE FINANCIAL MANAGEMENT - Aditiya, Roby; Sundari, Sri; Kartini, Kartini (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
Introduction: Transparent and accountable financial management in villages is fundamental to achieving effective governance and sustainable development at the grassroots level. This study aims to examine the influence of village apparatus quality and village facilitators' quality on the effectiveness of village financial management, while also analyzing the moderating role of the Village Consultative Body (BPD) in these relationships. Methods: The research employs a quantitative design, utilizing a structured survey distributed to 227 respondents, comprising village officials from South Sulawesi. The data were collected through online questionnaires shared via WhatsApp groups affiliated with village governance institutions and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM).Results: The results demonstrate that both the quality of village apparatus and village facilitators have a significant and positive impact on the quality of village financial management. Furthermore, the moderating role of BPD is found to significantly strengthen the relationship between village apparatus quality and financial management quality, while showing no moderating effect in the relationship between village assistants and financial management. These findings emphasize the strategic importance of enhancing both technical competence and collaborative oversight mechanisms in the governance of village finances. Theoretically, the integration of stewardship theory and agency theory offers a valuable lens for understanding how internal accountability and external supervision interact in shaping financial performance at the village level. This study contributes to the literature on public sector accounting and governance while offering policy recommendations for strengthening institutional frameworks in rural financial management. Keywords: Village Financial Management; Quality of Village Apparatus; Village Facilitators; Role of Village Consultative Body; Village Governance.